The incidence of the U.S.-China solar trade war - Sebastien Houde; Wenjun Wang (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
This paper investigates the distributional welfare effects of the recent trade war in the solar manufacturing sector resulting from the U.S. government-initiated trade tariffs against Chinese solar manufacturers. Our structural econometric model incorporates the vertical structure between upstream solar manufacturers and downstream solar installers. Counterfactual simulations show the tariffs had a small positive impact on U.S. manufacturers but a large negative impact on U.S. consumers and installers. Chinese manufacturers were also negatively economically affected. Overall, our results suggest the solar trade war led to large welfare losses in both countries and substantially slowed the adoption of solar photovoltaic technology.
Keywords: F14; L10; Q50; 330; Trade War; Solar Industry; Structural Econometric Model; Pass-Through